PERSEPSI ANGGOTA KEPOLISIAN TENTANG PENGELOLAAN SARANA DAN PRASARANA DI POLRES SAWAHLUNTO - Nining Ristia Ningsih (Jurnal Bahana Manajemen Pendidikan, 2014)
The porpose the research is how to management of facilities and basic facilities in the Polres Sawahlunto. The population in the research have 25 persons and because the population of the research only a little so all of the population to be sample. Instrument to collect the data inquiry is skala likert. The data is analysis mean skor every indicator. The result of research about that is good that is 3,97. It’s mean management of facilities and basic facilities in Polres Sawahlunto is good. Kata Kunci : Pengelolaan Sarana dan Prasarana